Martin Pebble - Sempé, Jean-Jacques 1932- (New York : Phaidon Press, 2006)
The story of a little boy whose face turns red for no particular reason. He meets Roddy Rackett, a little boy who keeps sneezing for no particular reason and a great friendship begins.
"First published in French as Marcellin Caillou by Éditions Denoël"--P. facing t.p.
boek
Keywords: Sempé, Jean-Jacques; Friendship -- Fiction